Through a gender lens: a scoping review of gendered experiences of AMR causes, burden and workforce in Nigeria - Ayodele Oluwakemi Majekodunmi; Mabel Kamweli Aworh; Esteller Mbadiwe; Kikiope Oluwafikemi Oluwarore; Mwapu Dika Ndahi; Dooshima Kwange (Frontiers in Global Women's Health)
BackgroundNigeria is among the countries with the top 10 highest burdens of infectious and zoonotic diseases worldwide. There is a correspondingly high rate of antimicrobial use and misuse in humans and animals, leading to antimicrobial resistance (AMR). Antimicrobial Resistance has a very high impact on women and girls as they form the majority of health workers at community level as well as being the main care givers and livestock custodians in the home, most likely to prescribe, purchase or administer antibiotics. However, there is very little information about gendered aspects of AMR in Nigeria. This paper undertakes a scoping review of antimicrobial resistance in Nigeria through a gender lens, looking at how sex and gender interact with antimicrobial resistance and efforts to mitigate its negative effects.MethodsA PRISMA scoping review was conducted for peer-reviewed articles published from the year 2000, describing studies in Nigeria on AMR, infectious disease treatment (including treatment seeking behaviour) and access and experiences of healthcare, which either take an explicit gender approach or include sex/gender as a key variable.ResultsStudies show clear gender differences in levels of disease risk/resistance, health-seeking behaviour and patterns of access to healthcare (including antimicrobials). Despite the fact that these patterns are clearly recognised across multiple publications in different settings, we did not find evidence of a corresponding analysis of how gender might reinforce these vulnerabilities.ConclusionsGendered aspects of infectious diseases, antimicrobial access and resistance are documented in Nigeria, albeit often incidentally. This data should be taken into account when considering the AMR problem and in the design of various interventions and the design of various interventions towards improving AMR and One Health in Nigeria.